Finite element numerical technique for magneto-micropolar nanofluid flow filled with chemically reactive casson fluid between parallel plates subjected to rotatory system with electrical and Hall currents. (2nd November 2022) - Shamshuddin, MD.; Ibrahim, W.
ABSTRACT: Steady electro-magnetohydrodynamic flow of a micropolar nanofluid in the attendance of reactive Casson fluid passing through parallel plates influenced by the rotating system with the implementation of Buongiorno nanofluid model is examined in this study. The momentum transport equation is enhanced by incorporating the electric field. In addition, the influence of reactive species has a vital role that is affecting the flow phenomenon in conjunction with a transverse magnetic field. The physical flow problem is modeled in the form of partial differential equations which are then transformed into nonlinear ordinary differential equations by using appropriate similarity functions and then solved numerically by the usage of the finite element method and procured results are visualized graphically. The outcomes for flow rate, microrotation, temperature, concentration, and engineering quantities distributions are shown in terms of graphical presentation. Momentum and angular momentum transport progressively in nature as the Casson parameter grows. Opposite results of microrotational profiles are found for electric currents in comparison with Hall currents. Both thermophoresis and Brownian motion are found to be significant effects in improving heat transportation phenomena in nanofluids. The existing available literature was utilized to test for validation of the numerical findings.